2018
DOI: 10.1175/mwr-d-18-0041.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Simulated Dropsondes to Understand Extreme Updrafts and Wind Speeds in Tropical Cyclones

Abstract: Extreme updrafts (≥10 m s−1) and wind gusts (≥90 m s−1) are ubiquitous within the low-level eyewall of intense tropical cyclones (TCs). Previous studies suggest that both of these features are associated with coherent subkilometer-scale vortices. Here, over 100 000 “virtual” dropsonde trajectories are examined within a large-eddy simulation (31.25-m horizontal grid spacing) of a category 5 hurricane in order to gain insight into the nature of these features and to better understand and interpret dropsonde obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 52 publications
(59 reference statements)
6
27
0
Order By: Relevance
“…For the thresholds of 20 m s −1 in vertical motion and 0.2 s −1 in vertical relative vorticity, the mean duration is 40 seconds and the longest is 138 s. We can conclude that the identified tornadoscale vortices are not repeatedly counted in the hourly output. The durations of tornado-scale vortices are consistent with observational and numerical studies (Wurman and Kosiba, 2018;Stern and Bryan, 2018). Figure 4a shows the location of the maximum vertical motions of the detected tornado-scale vortices including 89 vortices identified with the threshold of maximum vertical motion of 15 m s −1 .…”
Section: Nosupporting
confidence: 85%
See 2 more Smart Citations
“…For the thresholds of 20 m s −1 in vertical motion and 0.2 s −1 in vertical relative vorticity, the mean duration is 40 seconds and the longest is 138 s. We can conclude that the identified tornadoscale vortices are not repeatedly counted in the hourly output. The durations of tornado-scale vortices are consistent with observational and numerical studies (Wurman and Kosiba, 2018;Stern and Bryan, 2018). Figure 4a shows the location of the maximum vertical motions of the detected tornado-scale vortices including 89 vortices identified with the threshold of maximum vertical motion of 15 m s −1 .…”
Section: Nosupporting
confidence: 85%
“…Aberson et al (2006Aberson et al ( , 2017 analyzed the extreme updrafts in Hurricanes Isabel (2003) and Felix (2007) and suggested that the strong updrafts were likely associated with a small-scale vortex. The updraft of 22 m s −1 in Isabel was detected by a GPS dropwindsonde at just about 1300 m Stern and Bryan, 2018), while the updraft of 31 m s −1 in Hurricane Felix (2007) was observed at the flight altitude (∼ 3 km). Marks et al (2008) found that the EVM in Hurricane Hugo (1989) was associated with a max- imum vertical motion of 21 m s −1 and a maximum vertical relative vorticity of 0.125 s −1 at the altitude of 450 m. Based on these studies, a small-scale vortex associated with extreme wind speed can be treated as a tornado-scale vortex (Wurman and Kosiba, 2018;Wu et al, 2018).…”
Section: Identification Of Tsvsmentioning
confidence: 98%
See 1 more Smart Citation
“…High resolution simulation is necessary for detailed hurricane research, because some turbulence structures do not become resolved until a hundred meters or ten meters resolution is used. These turbulence structures will be the source of damage to offshore structures, such as wind farms and oil rigs, and coastal buildings [Worsnop et al, 2017a;Worsnop et al, 2017b;Bryan et al, 2017;Stern and Bryan, 2018]. Rotunno et al [2009] showed that the maximum wind speed in their tropical cyclone simulation showed a strong relation with the resolved three-dimensional turbulence structure scale.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in numerical models and computational capability have made it possible to simulate inner-core processes of the tropical cyclone (TC) with the grid spacing less than 1 km (e.g., Zhu 2008;Rotunno et al 2009;Bryan et al 2014;Stern and Bryan 2018; Rotunno and Bryan 2014;Green and Zhang 2015). The inner-core processes have significant implications to the dynamics of structure and intensity changes (Schubert et al 1999;Kossin and Schubert 2001).…”
Section: Introductionmentioning
confidence: 99%